2022
DOI: 10.3982/qe2260
|View full text |Cite
|
Sign up to set email alerts
|

Global trends in income inequality and income dynamics: New insights from GRID

Abstract: The Global Repository of Income Dynamics (GRID) is a new open‐access, cross‐country database that contains a wide range of micro statistics on income inequality, dynamics, and mobility. It has four key characteristics: it is built on micro panel data drawn from administrative records; it fully exploits the longitudinal dimension of the underlying data sets; it offers granular descriptions of income inequality and income dynamics for finely defined subpopulations; and it is designed from the ground up with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 60 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…Grouping observations, they further show how these moments vary with age and the level of earnings to help characterize labor market risks that workers face. Similar analyses have been implemented in many countries in the Global Repository of Income Dynamics (GRID) project, and findings are remarkably homogeneous across countries (Guvenen et al, 2022). Yet inferring earnings risk from administrative data comes with assumptions that are hard to test without subjective expectations data.…”
Section: Introductionmentioning
confidence: 82%
“…Grouping observations, they further show how these moments vary with age and the level of earnings to help characterize labor market risks that workers face. Similar analyses have been implemented in many countries in the Global Repository of Income Dynamics (GRID) project, and findings are remarkably homogeneous across countries (Guvenen et al, 2022). Yet inferring earnings risk from administrative data comes with assumptions that are hard to test without subjective expectations data.…”
Section: Introductionmentioning
confidence: 82%
“…The study is significant because it highlights the ongoing discrimination that women experience in both industrialized and developing nations (Akhtar et al, 2023;Apotsu et al, 2023;Guvenen et al, 2022). These studies show that women in the Global North spend a disproportionate amount of time on unpaid household chores in comparison to men, creating a double burden of duties because they also perform paid jobs.…”
Section: Introductionmentioning
confidence: 95%
“…We can enable women to follow their career aspirations, contribute to the economy, and ultimately remove barriers that impede advancement and advancement in society by making investments in accessible, high-quality childcare. Furthermore, research (Zagel & Van-Lancker, 2022;Guvenen et al, 2022;Herrera Torelli, 2013) has indicated that nations with higher rates of female labor force participation tend to see long-term economic gains from having adequate childcare choices.…”
Section: Gender Stereotypes and Unpaid Care Work In Ghanamentioning
confidence: 99%
“…1 Another drawback of survey data relative to administrative data is their smaller sample size which limits the granularity of the analysis. See Guvenen et al (2022) for a discussion.…”
Section: More Unequal We Stand? Inequality Dynamics In the United Sta...mentioning
confidence: 99%